Novel Technological Solutions for Assessment, Treatment, and Assistance in Mild Cognitive Impairment - Mancioppi, Gianmaria; Fiorini, Laura; Timpano Sportiello, Marco; Cavallo, Filippo (Frontiers in Neuroinformatics, 2019)
Alzheimer’s disease, and dementia, represents a common cause of disability and one of the most relevant challenges in the health world. In addition, this condition does not have, at moment, a pharmacological treatment that can stop the pathological progress. Mild cognitive impairment (MCI), defined as the borderline between normal aging and early dementia, represents a meaningful field of study because, in the transition to dementia, clinicians have defined a useful therapeutic window. Additionally, due to the lack of effective pharmacological interventions, recent years have seen an increase in research into new technological solutions to assess, stimulate, and assist patients afflicted with Alzheimer’s disease. This review aims to outline the use of information and communication technologies in the field studying MCI. Particularly, attention was focused on the use of sensors, both wearable and environmental; personal devices, including TV, PC, tablet, and smartphone; and finally, robots, both standalone and cloud networked. The idea is to depict the framework and describe the most meaningful research efforts in this field of study to display the current technologies available, describe the research objectives, and depict prospective future research. Regarding data sources, the research was conducted within three databases, PubMed Central, Web of Science, and Scopus, between January 2009 and December 2017. A total of 646 articles were found in the initial search. Accurate definition of the exclusion criteria and selection strategy allowed identification of the most relevant papers to use for the study. Finally, 56 papers were fully evaluated and included in this review.